Kernel structure in breads reduces in vitro starch digestion rate and estimated glycaemic potency only at high grain inclusion rates. (July 2019) - SRV, Akila; Mishra, Suman; Hardacre, Allan; Matia-Merino, Lara; Goh, Kelvin; Warren, Frederick; Monro, John
Highlights: The inclusion of grain particles > 1 mm in commercial breads is too low to reduce the rate of digestion of breads. Most whole grain breads sold in New Zealand do not have lower rates of starch digestion than white bread. The digestibility of starch in a bread may be reduced by increasing the grain particles content > 1 mm to 65% or greater. The glycaemic potency of breads may be reduced by decreasing the proportion of rapidly digested carbohydrate. Abstract: Although whole grain or wholemeal breads may be healthier than white breads because of their content of dietary fibre, vitamins and minerals, the relative glycaemic potency of New Zealand commercial breads is unknown. The contribution of grain structure to the rate and proportion of starch digested during human foregut digestion was estimated using in vitro digestion of breads differing in grain particle size and content. The bread samples were digested either as intact cubes or following homogenization to eliminate coarse (> 1 mm) grain structures. The relative glycaemic potency of the intact breads was estimated from glycaemic glucose equivalents (GGE) released during 120 min of in vitro digestion, and ranged from 34 GGE /100 g for white and most wholemeal breads to about 18 GGE /100 g for a rye bread containing 65% semi-intact kernels. Differences in GGE release between homogenized samples of the breads were due mainly to the wet weight proportion of digestible carbohydrate in the bread. In general, up to 35% of kibbled grain particles (>1 mm), as seen in most breads, had little effect on the rate of starch digestion whereas breads with > 65% of >1 mm particles (rye bread) significantly reduced the rate of starch digestion. It was concluded that the proportion of intact grains was insufficient to lower glycaemic potency in all but one of the breads (rye) evaluated. However, the glycaemic potency of breads may be reduced by lowering the proportion of carbohydrate, or increasing the proportion of larger grain particles, in the bread.